An analysis of green technologies’ development in Kazakhstan: problems and perspectives (Journal of Economic Research & Business Administration, 2016)
Green technologies are essential tools to ensure sustainable develop-ment of the economy. In this regard, the article deals with the problems and prospects of development of green technologies in the Republic of Kazakhstan. In the first part of the study, authors investigated more than 50 official sources of information, including laws, concepts, programs, events and reviews of major international organizations. The chronology of development of green technologies in Kazakhstan has been drawn up based on the analysis of secondary sources, which was divided into several stages, taking into account the key moments. Urgent problems and trends of development have also been identified in this area. In order to check the correctness of the analysis, expert interviewings were conducted with six experienced specialists, 2 of which are foreign. The article describes the methodology and the main results of the study in detail. Conclusions are classified on such aspects as the demand, technology, human resources, mentality and perspective of development, which are also supported by direct quotations from interviews of experts.